Robust control for Markovian jump delta operator systems with actuator saturation - Yang, Hongjiu; Li, Hongbo; Sun, Fuchun; Yuan, Yuan (European journal of control, 2014)
In this paper, robust stochastic stabilization problems for uncertain Markovian jump linear delta operator systems with actuator saturation are considered. The definition of the domain of attraction for a Markovian jump delta operator system in mean square sense is introduced to analyze the stochastic stability of the closed-loop system. By using a stochastic Lyapunov function which is dependent on the jump mode, design procedures for a mode-dependent state feedback controller are developed based on linear matrix inequality approach. A mode-independent state feedback controller is also designed by using a mode-independent Lyapunov function. Some simulation results are given to illustrate the effectiveness of the developed techniques.